Vaccines against Ovine Toxoplasmosis: History, Advances and Current status - Sulaiman, Rawaz Mhamad Jaza (Sulaimani Journal for Pure and Applied Sciences, 2014)
Toxoplasmosis is a common and wide spread global disease, caused by a protozoan parasite, Toxoplasma gondii. The condition afflicts both animal and human, causing abortion and congenital defects. Hence, it is of a huge veterinary and medical concern. With on-going researches, the mechanism of the disease is better appreciated nowadays. Developing a vaccine for veterinary use, more precisely for sheep will not only gain economic advantages, but it will also bring insight into discovering one for human use as well. Until now, the only available commercial vaccine in sheep is based on the attenuated T.gondii strain S48, known as Toxovac®, but the vaccine is only capable to provide a short immunity. Additionally, it is expensive and inappropriate to be applied in human. In recent years, different experimental studies have demonstrated the probability of developing a new vaccine. This paper tries to highlight the history of discovering the first commercial vaccine against toxoplasmosis in sheep, along with recent advances in the field and shining a light to the current status of vaccine trials.
Keywords: Toxoplasmosis; Immunity against Tgondi; Vaccines in sheep; DNA vaccines